The effect of the Baduanjin exercise on COVID-19-related anxiety, psychological well-being and lower back pain of college students during the pandemic - Keqiang Li; Tamara Walczak-Kozłowska; Mariusz Lipowski; Jianye Li; Daniel Krokosz; Yuying Su; Hongli Yu; Hongying Fan (BMC, 2022)
Abstract Background This study aimed to examine the effect of Baduanjin exercise on COVID-19-related anxiety, psychological well-being, and the lower back pain of college students during the coronavirus pandemic in China. Setting The study was carried out in a temporary experimental center of four universities in Wenzhou city in Zhejiang Province, China. Population 387 participants who were college students were allocated to two groups: the Baduanjin exercise group(BEG, n = 195); and the Control group(CG,n = 192). Methods In this randomized controlled trial,387 participants who were college students were randomly allocated in a 1:1 ratio to 12-week Baduanjin exercise group (BEG, n = 195)and 12-week Control group(CG,n = 192).CAS(Coronavirus Anxiety Scale), PWBS(Psychological Well-being Scale),NMQ( Nordic Musculoskeletal Questionnaire), was used to assess COVID-19-related anxiety, psychological well-being, and lower back pain at second times ( before and after the intervention). The paired t-test and an independent t-test (with a 95% confidence interval) was used to compare the outcome variables of the two groups. Results Within-group comparison, there was no significant difference in the control group before and after the intervention. In contrast, the Baduanjin group had a significant improvement before and after the intervention. Between-group comparison, the Baduanjin group had a significant difference from the control group. The intervention effect on the Baduanjin exercise group was remarkably better than that of the control group (p < 0.05). Participants in the Baduanjin group significantly improved the corvid-19-related anxiety score decreased from ( 5.22 ± 0.45 to 5.07 ± 0.27, p < 0.05). The total psychological well-being score increased from (70.11 ± 8.65 to 84.12 ± 7.38,p < 0.05) and the prevalence of low back pain decreased from (22.45 ± 1.67 to 18.35 ± 1.05, p < 0.05) among college students. Conclusion During the pandemic, the Baduanjin exercise contributes to the reduction of the perceived anxiety related to COVID-19, decreases the prevalence of the lower back pain, and improves the psychological well-being of college students. Trial registration Clinicaltrials.gov, NCT04432038. Registered on June 16, 2020.